Decreased glycolysis induced dysfunction of NK cells in Henoch-Schonlein purpura patients - Wenjia Chai (BMC Immunology, 2020)
Abstract Background Henoch-Schonlein purpura (HSP) is the most common systemic vasculitis of the childhood. However, its mechanisms and pathogenesis still need more exploration. Natural killer (NK) cells are innate lymphocytes, and there is a growing appreciation that cellular metabolism is important in determining the immune responsiveness of lymphocytes. Thus, we aimed to analyze the NK cells phenotype and explore the association between glucose metabolism and NK cells function in HSP patients. Results A total number of 64 HSP patients and 34 healthy children were included. The HSP patients were divided into two groups according to whether accompanied with nephritis or not. NK cells in HSP patients without nephritis showed a reduced frequency in peripheral blood, a down-regulated expression of activating receptors both NKp30 and NKp46, and an attenuated cytotoxic function against tumor cells. In addition, the function impairment of NK cells was shown to exacerbate in HSPN. Our data further revealed an aberrant metabolic reprogramming of NK cells in HSP patients. Upon stimulation with cytokines (IL-15, IL-12 and IL-2), NK cells from healthy controls switched to an elevated glycolysis rate to support their effector function. By contrast, the glycolysis rate of activated NK cells in HSP group was not significantly up-regulated from the resting level possibly owing to the inhibition of mTORC1. Conclusions Our study found that HSP patients were accompanied with dysfunction of NK cells. We concluded that the dysfunction of NK cells in HSP patients was induced with a decreased glycolysis rate and suggested that metabolic reprogramming of NK cells might be a player in the pathogenesis of HSP.